The implications of the 2001 Primary Health Care Strategy for providers and consumers : a thesis presented in partial fulfillment of the requirements for the degree of Master of Philosophy in Nursing at Massey University, Albany, New Zealand - Martin, Julie (Massey University, 2002)
AIM AND RESEARCH QUESTION To discuss The Primary Health Care Strategy (King, 2001) and its implications for providers and consumers. The research question is: What are the implications of the 2001 Primary Health Care Strategy for providers and consumers METHODOLOGY Applied policy qualitative analysis using the 'framework' approach. This non-contact approach involved generating data from the strategy document by identifying themes that related to the research question, coding the data according to the themes and then mapping and interpreting the data. The process involved a systematic but flexible approach to determine the meaning, relevance and connections of the data and the themes. The themes of 'provider' and 'consumer' were identified a priori and guided the process to identify the three key themes of funding, services and skills. Part way through the process two further categories were identified in order to fully answer the research question. These included: Implications of the strategy for consumers; and implications of the strategy for providers. A theoretical framework informed the discussion for both categories. RESULTS The findings demonstrate that the strategy has significant implications for providers and consumers. It shows that the vision and the key directions outlined by King (2001) are achievable but require a different process than that outlined in the document. The findings suggest that the most effective way to achieve these are to: Target disadvantaged groups and providers who are willing to work with those groups; strengthen nursing' s professional identity by establishing primary health care nursing models; assign nurses the responsibility to deliver population health activities; and address the structures and payment mechanisms in General Practice.